Real‐world outcomes of FOLFIRINOX vs gemcitabine and nab‐paclitaxel in advanced pancreatic cancer: A population‐based propensity score‐weighted analysis. (13th November 2019) - Chan, Kelvin K. W.; Guo, Helen; Cheng, Sierra; Beca, Jaclyn M.; Redmond‐Misner, Ruby; Isaranuwatchai, Wanrudee; Qiao, Lucy; Earle, Craig; Berry, Scott R.; Biagi, James J.; Welch, Stephen; Meyers, Brandon M.; et al.
Abstract: Background: In Ontario, FOLFIRINOX (FFX) and gemcitabine + nab‐paclitaxel (GnP) have been publicly funded for first‐line unresectable locally advanced pancreatic cancer (uLAPC) or metastatic pancreatic cancer (mPC) since April 2015. We examined the real‐world effectiveness and safety of FFX vs GnP for advanced pancreatic cancer, and in uLAPC and mPC. Methods: Patients receiving first‐line FFX or GnP from April 2015 to March 2017 were identified in the New Drug Funding Program database. Baseline characteristics and outcomes were obtained through the Ontario Cancer Registry and other population‐based databases. Overall survival (OS) was assessed using Kaplan‐Meier and weighted Cox proportional hazard models, weighted by the inverse propensity score adjusting for baseline characteristics. Weighted odds ratio (OR) for hospitalization and emergency department visits (EDV) were estimated from weighted logistic regression models. Results: For 1130 patients (632 FFX, 498 GnP), crude median OS was 9.6 and 6.1 months for FFX and GnP, respectively. Weighted OS was improved for FFX vs GnP (HR = 0.77, 0.70‐0.85). Less frequent EDV and hospitalization were observed in FFX (EDV: 67.8%; Hospitalization: 49.2%) than GnP (EDV: 77.7%; Hospitalization: 59.3%). More frequent febrile neutropenia‐related hospitalization was observed in FFX (5.8%) than GnP (3.3%). Risk of EDV and hospitalization were significantly lower for FFX vs GnP (EDV: OR = 0.68, P  = .0001; Hospitalization: OR = 0.76, P  = .002), whereas the risk of febrile neutropenia‐related hospitalization was significantly higher (OR = 2.12, P  = .001). Outcomes for uLAPC and mPC were similar. Conclusion: In the real world, FFX had longer OS, less frequent all‐cause EDV and all‐cause hospitalization, but more febrile neutropenia‐related hospitalization compared to GnP. Abstract : In the real world, implementation of universal public funding of FOLFIRINOX for metastatic pancreatic cancer was associated with improved overall survival, less frequent all‐cause emergency department visits, less frequent all‐cause hospitalization, but increased febrile neutropenia‐related hospitalization compared to patients treated with gemcitabine + nab‐paclitaxel. Expanding funding to include unresectable locally advanced pancreatic cancer was associated with a similar trend in benefits, but with improved absolute survival.